Peningkatan Kapasitas UMKM Pempek Nyai Dalam Mengembangkan Makanan Khas Palembang Di Kota Bengkulu Melalui Pemasaran Digital - Oktavia, Ferda; Kusumawarty, Pratiwi; Afriani, Sulisti; Yustanti, Nirta Vera; Revolina, Elya (LPPM Universitas Dehasen Bengkulu, 2025)
This community service activity aims to increase the capacity of the Pempek Nyai UMKM in developing Palembang's signature food in Bengkulu City through the implementation of digital marketing strategies. Through mentoring and training focused on the use of social media, attractive product packaging, and strengthening brand identity, the Pempek Nyai UMKM was able to expand its market reach and increase product sales. The results of the activity showed that the implementation of digital marketing had a positive impact on the competitiveness and independence of business actors, so that it could become a model for sustainable empowerment of local UMKM. The implementation method included problem identification, training on product diversification and packaging, mentoring in utilizing social media and marketplace platforms, and business performance evaluation. The results of this program showed an increase in product variety, more attractive packaging, and increased sales through digital platforms. This program contributed to increasing the competitiveness of Pempek Nyai and serves as a model for empowering UMKM based on local culinary products.